ANALISIS RISIKO PENYALURAN OBAT PADA BAGIAN INSTALASI FARMASI DI FASILITAS PELAYANAN KESEHATAN - Novita, Dian; Al Fauzain, Al Fauzain; Fitri, Aznila; Afrima Yenni, Ririn (Ensiklopedia of Journal, 2022)
Drug distribution is a crucial aspect of drug management in healthcare facilities. However, this process often faces various issues that may affect the quality and continuity of drug distribution. This study aims to analyze the implementation of risk management in the drug distribution process at the pharmacy installation in healthcare facilities. The method used in this study is a systematic literature review with a traditional review approach. Article searches were conducted through four databases, namely Google Scholar, Springer Link, PubMed, and Elsevier, using the keywords "distribution of drugs AND risk management AND pharmaceutical services AND health care facilities." The results indicate several risks that may occur in drug distribution, such as dead stock, expired drugs, distribution errors, and discrepancies between the received and required quantities of drugs. Furthermore, factors contributing to these risks include storage system errors, human errors, and non-compliance with established procedures. Risk evaluation revealed that dead stock and distribution errors have a very high impact. This study recommends the need for a more systematic and structured risk management implementation in every healthcare facility to mitigate the impacts of identified risks.Keywords: Risk Management, Drug Distribution